Analyzing Healthcare Facility Resilience: Scientometric Review and Knowledge Map - Li, Lingzhi; Liao, Shuni; Yuan, Jingfeng; Wang, Endong; She, Jianjun (Frontiers in Public Health, 2021)
In contemporary “high-risk” society, unexpected disasters (epidemics and extreme weather) and chronic pressures (aging problems) put tremendous pressure on healthcare facilities. Enhancing the healthcare facilities’ resilience ability to resist, absorb, and respond to disaster disruptions is urgent. This study presents a scientometric review for healthcare facility resilience research. A total of 323 relevant articles published between 2000 and 2020, collected from WoS core collection database and Scopus database, were reviewed and analyzed. The results indicated that research on resilience in healthcare facility went through three development periods, and the research involved countries or institutions that are relatively scattered. The studies have been focused on the subject categories of engineering and public and environmental and occupational health. The keywords of “resilience,” “hospital,” “healthcare,” “disaster,” and “earthquake” had the most frequency. Furthermore, based on the literature co-citation networks and content analysis, the detected nine co-citation clusters were grouped into five knowledge domains: climate change impact, the impact of wars and epidemics, resilience assessment of healthcare facility, vulnerability assessment, and the application of technologies. Moreover, the timeline view of literature reflected the evolution of each domain. Finally, a knowledge map for resilience of healthcare facility was put forward, in which critical research contents, current knowledge gaps, and future research work were discussed. This contribution will promote researchers and practitioners to detect the hot topics, fill the knowledge gaps, and extend the body of research on resilience in healthcare facility.